2011
DOI: 10.1190/1.3560167
|View full text |Cite
|
Sign up to set email alerts
|

Gabor deconvolution: Estimating reflectivity by nonstationary deconvolution of seismic data

Abstract: We have extended the method of stationary spiking deconvolution of seismic data to the context of nonstationary signals in which the nonstationarity is due to attenuation processes. As in the stationary case, we have assumed a statistically white reflectivity and a minimum-phase source and attenuation process. This extension is based on a nonstationary convolutional model, which we have developed and related to the stationary convolutional model. To facilitate our method, we have devised a simple numerical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(79 citation statements)
references
References 27 publications
0
74
0
Order By: Relevance
“…Dennis Gabor in 1946 brought up the idea of applying Fourier analysis in partition sense [2] . A series of non-stationary seismic trace is divided into smaller signal packet which was localized by a certain window.…”
Section: Methodsmentioning
confidence: 99%
“…Dennis Gabor in 1946 brought up the idea of applying Fourier analysis in partition sense [2] . A series of non-stationary seismic trace is divided into smaller signal packet which was localized by a certain window.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a local analysis scheme is necessary to yield a time-frequency representation for the time-variant system. Among a variety of local analysis based algorithms for estimating the object reflectivity in the presence of nonstationary systems, Gabor nonstationary deconvolution has demonstrated success in attenuation compensation and phase correction for seismograms [34]. Through the partition of unity (POU) windowing scheme, the Gabor algorithm is able to minimize the energy loss during the forward and inverse Gabor transform and achieve an invertible dual-domain transformation.…”
Section: Gabor Transform Of Nonstationary Convolutional Modelmentioning
confidence: 99%
“…There are various ways to estimate the attenuation function in the Gabor domain. In particular, Margrave et al [34,56] reported that the hyperbolic smoothing approach is robust and able to yield a consistent estimate of the Gabor magnitude spectrum of the propagating wavelet. Hyperbolic smoothing is essentially based on the theory that the amplitude spectrum of attenuation can be described by a constant Q model as…”
Section: Gabor Deconvolutionmentioning
confidence: 99%
See 2 more Smart Citations